Gastrointestinal stromal tumors mimicking as gynecological tumors-A case series - Kiran Trivedi; Shabnam Toppo; Apoorwa Sharma; Rohit Kumar Jha; Binit Bharati; Pushpanjali; Tulika Sinha (Journal of Family Medicine and Primary Care)
Gastrointestinal stromal tumors (GISTs) are rare mesenchymal tumors that arise from interstitial cells of Cajal. Due to vague presentation, location and confusing imaging studies, they tend to mimic gynaecological tumors. They usually diagnosed intra-operative and histopathology followed by tumor specific receptors such as KIT, CD34, CD 117 and DOG 1 are mainstay of diagnosis of GIST. Prognosis of GISTs depends on mitotic rate, tumor size and organ of origin. Resection of mass with tumor free margins is the target of treatment. L ymphadenectomy is not routine. Chemotherapy with tyrosine kinase inhibitors such as Imatinib, Dasatinib, Sorafenib and follow- up depend upon risk category. In this case series, there were four cases with vague symptoms misdiagnosed as gynaecological tumors are reviewed. Preoperatively tumors assumed to be of gynaecological origin were found to be case of GISTs intra-operatively and confirmed by presence of cajal’s cells histopathology and mainly by DOG 1, CD117 and tyrosine kinase inhibitor receptors on immunohistochemistry. All belonged to high risk category of GISTs. Any abdomino-pelvic mass detected on ultrasonography and with unusual presentation presenting at primary health centre the possibility of non-gynecological tumors especially GISTs should be kept in mind and should be referred to higher centres for further investigation and proper management.